2022
DOI: 10.3390/ijerph191912565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Oral Hygiene-Related Mobile Apps for Children in Sub-Saharan Africa

Abstract: In sub-Saharan Africa, oral health is a real epidemiological challenge. Mobile applications represent a hope for the learning of oral hygiene in children and the fight against oral diseases. This study overviews and assesses the quality of mobile applications linked to oral hygiene for children currently featured on the iOS and Android stores in sub-Saharan Africa. Ten oral health professionals (OHP) used the French Mobile App Rating Scale (MARS-F) to rate 15 selected applications. The highest MARS-F scores fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Mobile apps within the context of mHealth interventions are also a potential tool for educating parents about their children's oral health, as supported by several randomised control trials (15)(16)(17). Majority of the dental caries prevention apps focus on providing oral hygiene education and information for different age groups including children or adults (18)(19)(20). However, a recent review (18) identified a significant gap in the availability of apps that are specifically designed to support parents of young children in preventing dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile apps within the context of mHealth interventions are also a potential tool for educating parents about their children's oral health, as supported by several randomised control trials (15)(16)(17). Majority of the dental caries prevention apps focus on providing oral hygiene education and information for different age groups including children or adults (18)(19)(20). However, a recent review (18) identified a significant gap in the availability of apps that are specifically designed to support parents of young children in preventing dental caries.…”
Section: Introductionmentioning
confidence: 99%
“…The studies belonged to four categories: randomized controlled clinical trials [41][42][43][44][45][46][47][48][49][50][51], cross-sectional studies [52], before-after (pre-post) studies with no control group [53], and observational studies [54][55][56][57][58][59][60]. Table S3 (Supplementary Materials) shows the studies excluded from this review and the reasons for exclusion [30][31][32][33][34][35][36][37][38][39][40].…”
Section: Resultsmentioning
confidence: 99%
“…24 In another survey, Kanoute et al assessed the quality of different mobile game applications currently available that are linked to oral hygiene measures for children through a survey among oral health professionals who recommended their use and rated them positively. 25 A recent study investigated the usage of a smartphone app for improving manual toothbrushing via a gravitation sensor by measuring the plaque and gingival indices through a randomized controlled trial, showing promising results. 26 Similarly, comparison of A-R-assisted toothbrushing via a mobile app with manual brushing was done among 247 children by assessing plaque scores and Visual biofilm index by Desai et al 27 and measuring toothbrushing duration and distribution by Jacobson et al 28 However, to the best of our knowledge, none of the recent studies have evaluated microbiological evidence of bacterial load reduction via A-R-assisted toothbrushing with a supporting fluorescence data added as a measurable outcome.…”
Section: Discussionmentioning
confidence: 99%